WEB-BASED COFFEE BEAN STOCK INFORMATION SYSTEM AT NOMAD COFFEE ROASTERY - Karel, Risdianto; Montolalu, Chriestie Ellyanne Juliet Clara; Latumakulita, Luther Alexander (Indonesian Journal of Intelligence Data Science, 2022)
The development of internet technology in this day and age is accelerating. The internet makes it easy for humans to access information and do various things. We can find the information we need and we can expand our communication network using the sophistication of technology. The same is the case with roasting coffee bean stock information at Nomad Coffee Roastery which is still less effective. The purpose of this research is to create a system of incoming stock data and outgoing stock of coffee beans and information about the availability status of roasting coffee beans at Nomad Coffee Roastery based on the website as a means of information and communication between nomad owners and buyers. The method used in designing this system is the waterfall method. The resulting program is a Web-based Roasting Coffee Bean Stock Information system that is able to provide stock data information and information about the availability status of roasting coffee beans at Nomad Coffee Roastery.